Mustafayeva, Fidan - (:unkn) unknown (My University, 2026)
Fidan Mustafayeva is an Associate Professor in the Department of Basics of Architecture at the Azerbaijan University of Architecture and Construction (AzUAC). Her teaching areas include Fundamentals of Planning, Fundamentals of Design, Architectural Design, and Computer-Aided Design. She is the author of more than 40 scientific publications, including the book The Architecture of Hydraulic Structures. Her current research focuses on the theory and practice of sustainable architecture for recreational areas in large cities.